Determinants of social support among people living with HIV in Nigeria–a multicenter cross-sectional study - Babalola, Oluwatobi E.; Badru, Oluwaseun A.; Bain, Luchuo E.; Adeagbo, Oluwafemi (Frontiers in Public Health, 2023)
Background: More than 38.4 million people were living with HIV worldwide in 2021. Sub-Saharan Africa bears two-thirds of the burden, with Nigeria having nearly two million people living with HIV (PLWH). Social support from social networks such as family and friends improve the quality of life, and reduces enacted and perceived stigma, but social support for PLWH remains suboptimal in Nigeria. This study aimed to assess the prevalence of social support and associated factors among PLWH in Nigeria and to test whether stigma reduces types of social support. Methods: This cross-sectional study was conducted in Lagos State, Nigeria, between the months of June and July 2021. A total of 400 PLWH were surveyed across six health facilities providing antiretroviral therapy. Social support (family, friends, and significant others) and stigma were measured with the Multidimensional Scale of Perceived Social Support and Berger’s HIV Stigma Scale, respectively. Binary logistic regression was used to identify determinants of social support. Results: More than half (50.3%) of the respondents had adequate social support overall. The prevalence of family, friends, and significant others support was 54.3%, 50.5%, and 54.8%, respectively. Stigma (Adjusted Odds Ratio [AOR]: 0.945; 95% Confidence Interval [CI]: 0.905-0.987) was negatively associated with adequate friend support. Female gender (AOR: 6.411; 95% CI: 1.089-37.742), higher income (AOR: 42.461; 95% CI: 1.452-1241.448), and seropositive disclosure (AOR: 0.028; 95% CI: 0.001-0.719) were associated with adequate significant others support. Stigma (AOR:0.932; 95% CI: 0.883-0.983) was negatively associated with adequate support overall. Our findings corroborate the social support theory, as stigma reduces the chance of receiving social support. Conclusions: PLWH that enjoy support from families or friends were less likely to be affected by HIV-related stigma. More support is needed by PLWH from family, friends, and significant others to improve the quality of life and reduce stigma among PLWH in Lagos State.